A joint molecular networking study of a Smenospongia sponge and a cyanobacterial bloom revealed new antiproliferative chlorinated polyketides. Issue 11 (23rd April 2019) - Teta, Roberta; Della Sala, Gerardo; Esposito, Germana; Via, Christopher W.; Mazzoccoli, Carmela; Piccoli, Claudia; Bertin, Matthew J.; Costantino, Valeria; Mangoni, Alfonso
Abstract : Feature based molecular networking was used to compare chlorinated metabolites of S. aurea and Trichodesmium sp. and revealed four new antiproliferative polyketides. Abstract : The bloom-forming cyanobacterium Trichodesmium sp. has been recently shown to produce some of the chlorinated peptides/polyketides previously isolated from the marine sponge Smenospongia aurea . A comparative analysis of extracts from S. aurea and Trichodesmium sp. was performed using tandem mass spectrometry-based molecular networking. The analysis, specifically targeted to chlorinated metabolites, showed that many of them are common to the two organisms, but also that some general differences exist between the two metabolomes. Following this analysis, six new chlorinated metabolites were isolated and their structures were elucidated: four polyketides, smenolactones A–D (1–4 ) from S. aurea, and two new conulothiazole analogues, isoconulothiazole B (5 ) and conulothiazole C (6 ) from Trichodesmium sp. The absolute configuration of smenolactone C (3 ) was determined by taking advantage of the conformational rigidity of open 1, 3-disubstituted alkyl chains. The antiproliferative activity of smenolactones was evaluated on three tumor cell lines, and they were active at low-micromolar or sub-micromolar concentrations.